Misplaced intra uterine devices: a rare case of vaginal entrapment - Grover, Anshul; Mehta, Sumita; Mann, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Intra uterine devices (IUD) are the second most common accepted methods of contraception worldwide after sterilization. It is a long acting reversible contraceptive (LARC) which is now being promoted as a simpler, safer and effective method of contraception for those women who do not want a permanent method of contraception. Missing thread is the most common complaint seen within 6 weeks of insertion and may be the only presentation of misplaced IUD. Most women who spontaneously expel the IUD are unaware of the situation. We are presenting a case of misplaced IUD which was partially expelled and got embedded in the vagina which is a rare site of misplaced IUD.